HOMBRES QUE TRABAJAN SOBRE COSA SUYA”: LABOR ARTESANAL EN LA PROVINCIA DEL SOCORRO, NUEVA GRANADA, SIGLOS XVIII Y XIX. - Álvarez Orozco, René (2007)
This article refers to the history of the artisan activity in the province of Socorro, Nueva Granada, during the 18th century and beginnings of the 19th century. Initially, a conceptual reflection will be made regarding the work of the artisan, parting from the concept of home production proposed by Max Weber.